A study of the risk factors for phlebitis in patients stratified using the acute physiology and chronic health evaluation II score and admitted to the intensive care unit: A post hoc analysis of the AMOR-VENUS study - Kishihara, Yuki; Yasuda, Hideto; Moriya, Takashi; Kashiura, Masahiro; Koike, Midori; Kotani, Yuki; Kondo, Natsuki; Sekine, Kosuke; Shime, Nobuaki; Morikane, Keita; Abe, Takayuki (Frontiers in Medicine, 2022)
Introduction Peripheral intravascular catheters (PIVCs) are inserted in most patients admitted to the intensive care unit (ICU). Previous research has discussed various risk factors for phlebitis, which is one of the complications of PIVCs. However, previous studies have not investigated the risk factors based on the patient’s severity of illness, such as the Acute Physiology and Chronic Health Evaluation (APACHE) Ⅱ score. Different treatments can be used based on the relationship of risk factors to the illness severity to avoid phlebitis. Therefore, in this study, we investigate whether the risk factors for phlebitis vary depending on the APACHE Ⅱ score. Materials and Methods This study was a post-hoc analysis of the AMOR-VENUS study involving 23 ICUs in Japan. We included patients with age ≥ 18 years and consecutive admissions to the ICU with PIVCs inserted during ICU admission. The primary outcome was phlebitis, and the objective was the identification of the risk factors evaluated by hazard ratio (HR) and 95% confidence interval (CI). The cut-off value of the APACHE Ⅱ score was set as ≤ 15 (group 1), 16–25 (group 2), and ≥ 26 (group 3). Multivariable marginal Cox regression analysis was performed for each group using the presumed risk factors. Results A total of 1,251 patients and 3,267 PIVCs were analyzed. Multivariable marginal Cox regression analysis reveals that there were statistically significant differences among the following variables evaluated HR (95%CI): (i) in group 1, standardized drug administration measures (HR, 0.4 [0.17–0.9]; p = 0.03) and nicardipine administration (HR, 2.25 [1.35–3.75]; p < 0.01); (ii) in group 2, insertion in the upper arm using the forearm as a reference (HR, 0.41 [0.2–0.83]; p = 0.01), specified polyurethane catheter using polyurethane as a reference (HR, 0.56 [0.34–0.92]; p=0.02), nicardipine (HR, 1.9 [1.16–3.12]; p = 0.01), and noradrenaline administration (HR, 3.0 [1.52–5.88]; p < 0.01); (iii) in group 3, noradrenaline administration (HR, 3.39 [1.14–10.1]; p = 0.03). Conclusion We found that phlebitis risk factors varied according to illness severity. By considering these different risk factors, different treatments may be provided to avoid phlebitis based on the patient’s severity of illness.